First trimester pregnancy-associated plasma protein-A and birth weight. (March 2016) - Baer, Rebecca J.; Lyell, Deirdre J.; Norton, Mary E.; Currier, Robert J.; Jelliffe-Pawlowski, Laura L.
Abstract: Objective: To evaluate first trimester pregnancy-associated plasma protein-A (PAPP-A) and birth weight percentile. Study design: Included were women who underwent first trimester prenatal screening through the California Prenatal Screening Program with expected dates of delivery between August 2009 and December 2010, linked birth certificate and hospital discharge records, known birth weight, and no chromosomal abnormality ( n = 134.105). PAPP-A results were reported as multiples of the median. The frequency of small or large for gestational age (SGA, ≤10%; LGA, ≥90%) versus appropriately grown for gestational age birth was examined by PAPP-A percentile. Patterns were studied by gestational age at delivery. Relative risks (RRs) and their 95% confidence intervals were adjusted for race/ethnicity. Results: Women with PAPP-A ≤10th percentile and an infant born after 32 weeks were increasingly more likely to have an SGA infant (adj RRs 1.5–4.6) as the PAPP-A percentile declined, and were increasingly less like to have an LGA infant born at term (adj RRs 0.5–0.7) compared to women with PAPP-A measurement >10th to <90th percentile. PAPP-A ≥90th percentile was protective for SGA among infants born after 32 weeks gestation (adj RRs 0.3–0.7) and was associated with LGA among infants born at term (adj RRs 1.2–8.2). Conclusion: Women with PAPP-A ≤10th percentile are more likely to have an SGA infant at all gestational ages. PAPP-A ≥90th percentile is protective against SGA and is associated with an increased risk of LGA for infants born after 32 weeks gestation.